INVENTORY OF CULTURAL ACTIVITIES AND DEVELOPMENT OF STRATEGIES FOR THE PREPARATION OF CULTURAL DATA FRAMEWORK FOR THE SPECIAL REGION OF YOGYAKARTA - Sri Wahyuni; Siti Noor Aini; Firda Diartika (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
The DIY Privileges Policy requires the availability of structured cultural data to support the formulation and evaluation of cultural development. This study compiles an inventory of DIY cultural activities in 2013–2021 and analyzes them through a descriptive-qualitative approach to formulate the DIY Cultural Data Framework. The results of the study show that DIY cultural activities are grouped based on three goals, namely increasing the capacity of cultural resources, developing cultural events, and developing cultural facilities and infrastructure. The development of cultural facilities is the category of activities with the largest budget realization, followed by increasing human resource capacity and organizing events. The findings also indicate a wide diversity of cultural programs that have not been harmonized across OPDs. The SWOT analysis identifies strengths in the form of privilege legitimacy and community networks, as well as weaknesses related to data fragmentation and apparatus capacity variations. Through the SO, WO, ST, and WT strategies, this study formulates the direction of strengthening data governance, digitizing cultural documentation, and increasing institutional capacity.